ANTI-RADICAL ACTIVITIES OF XANTHONES AND FLAVONOIDS FROM GARCINIA SCHOMBURGKIANA - Meechai, Imron; Phupong, Worrapong; Chunglok, Warangkana; Meepowpan, Puttinan (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The present study aimed to isolate and identify the phytochemical constituents of Garcinia schomburgkiana branches and evaluate the antioxidant activity of the compounds. Methods: The chromatographic and spectroscopic (UV, IR, NMR and MS) techniques were used for the isolation and elucidation of the compounds, respectively. The antioxidant activity of the isolated compounds was examined through DPPH, ABTS, nitric oxide and hydroxyl radical scavenging assay. Results: The (-)-5,7,3′,5′-tetrahydroxyflavanone (1), which was firstly found in the Garcinia species, together with kaempferol (2), (-)-dihydrokaempferol (3), euxanthone (4), gentisein (5) and norathyriol (6) were isolated from G. schomburgkiana. Among the isolated compounds, compound 1 and 6 exhibited the highest potential for anti-radical activities. Conclusion: Compound 1 could be used as the chemotaxonomic marker of G. schomburgkiana. The branches of G. schomburgkiana could be the alternative source of the antioxidants. The possible inhibitory mechanisms were proposed through the action of electron transfer, chelation, and nitrosylation.